2021
DOI: 10.1108/heswbl-07-2020-0161
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers' acquisition of scientific knowledge and scientific skills through inquiry-based laboratory activity

Abstract: PurposeScientific inquiry is a leading methodology that promotes science process skills to acquire scientific knowledge. There is evidence that primary school teachers have difficulties introducing inquiry-based activities in their classrooms. Hence, adequate teacher instruction in inquiry methodology is important to apply inquiry-based activities in school science lessons. This work aims to analyse if pre-service teachers succeeded in developing scientific knowledge and scientific skills through the applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The importance of collaboration seems to be confirmed in this study. Additionally, this study's findings are in line with the findings in Yustina et al's [24], and Valls-Bautista et al's [35] studies, which indicate that intervention strategies improve students' inquiry-based skills. However, Ozer and Sarıbaş [37] indicate that intervention strategies only improve some of the students' inquiry-based skills, especially if the intervention is administered over a short period of time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The importance of collaboration seems to be confirmed in this study. Additionally, this study's findings are in line with the findings in Yustina et al's [24], and Valls-Bautista et al's [35] studies, which indicate that intervention strategies improve students' inquiry-based skills. However, Ozer and Sarıbaş [37] indicate that intervention strategies only improve some of the students' inquiry-based skills, especially if the intervention is administered over a short period of time.…”
Section: Discussionsupporting
confidence: 90%
“…By actively seeking out, understanding, and incorporating these variables in design processes, students can enhance their overall effectiveness in the experimental design process. Valls-Bautista et al [35] and Garcıa-Carmona et al [36] also found that students had shortcomings in identifying variables and in planning the complete development of a guided scientific inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…As PSETs experience cognitive conflict, the instructor needs to provide scaffolding that helps connect phenomena to prior knowledge or experiences. Finally, the last step involves supporting PSETs in proposing investigative questions by linking cognitive conflict encountered during sensemaking to prior knowledge or experiences (Furtak & Penuel, 2019; Kang et al, 2016; Valls‐Bautista et al, 2021). For the purposes of this study, a previously conducted pilot study provides insight into how the anchoring phenomenon routine is supported during student‐based discussions that precede laboratory instruction (Hinde, 2019, p. 57).…”
Section: Methodsmentioning
confidence: 99%
“…According to Valls-Bautista, Solé-Llussà and Casanoves [43], the teachers in the basic education have difficulty to work with dynamic methodologies in their classes. Therefore, the introduction of this type of activities during the pre-service period of formation can facilitate the applicability of similar practices in the school context.…”
Section: Activity Developmentmentioning
confidence: 99%